Ferromagnetic resonance investigation of Py/Cr multilayer system - (:unkn) unknown (AIP Publishing, 2011)
The multilayer thin films consisting of alternating stacks of ferromagnetic Permalloy (Py) and ultra thin non-magnetic (sub-nanometer) spacer (Cr) layers have been investigated by using ferromagnetic resonance (FMR) and dc magnetization measurement techniques. The non-magnetic spacer layer thickness changes from 0.5 angstrom to 2.5 angstrom by 0.5 angstrom steps. Polycrystalline composite metallic films were grown on Si substrate by usual magnetron sputtering techniques at UHV conditions. The magnetic hysteresis curves were recorded by conventional dc magnetization. The ac and dc magnetic properties were investigated by using ferromagnetic resonance. FMR measurements were carried out for different directions of external dc magnetic field in order to search magnetic anisotropy. Two strong and well defined peaks (acoustic and optic mode) were observed in FMR spectrum as the magnetic field direction approaches to the film normal. Their positions and relative intensities helped to characterize coupling species. The magnetic parameters have been deduced by using a theoretical model. It has been found that the exchange coupling parameter between ferromagnetic layers through non-magnetic Cr spacer is ferromagnetic in nature and strongly decreases with increasing spacer layer thickness. The magnetic anisotropy parameters strictly depend on magnetic layer thickness while the dc magnetization is almost constant for a few nanometer thick Permalloy as well. We observed only ferromagnetic coupling between ferromagnetic layers in all samples. (C) 2011 American Institute of Physics. [doi: 10.1063/1.3613700]
Keywords: MAGNETIC-ANISOTROPY